The Effect of Fort Games on Physical Fitness - Haykal Ibham Hilmi; Hijrah Maulidiah Afifah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to examine the effect of the traditional Bentengan (fort) game on improving the physical fitness of fourth-grade students at Pakintelan 02 State Elementary School. The research employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model. The sample consisted of 21 students selected through total sampling. Data were collected using the Nusantara Student Fitness Test (TKPN), which includes sit-up, V-sit reach, squat thrust, and pacer test components. The data were analyzed using descriptive statistics and inferential analysis, including normality, homogeneity, and paired sample t-test at a significance level of 0.05. The results showed that students’ physical fitness improved after the treatment, as indicated by increased mean scores across all test components and a shift in fitness categories from predominantly poor and very poor in the pretest to fair and good in the posttest. The paired sample t-test revealed a significant difference between pretest and posttest results (p < 0.05), confirming the effectiveness of the Bentengan game in enhancing students’ physical fitness. In conclusion, the traditional Bentengan game can be used as an innovative, engaging, and effective learning method to improve physical fitness among elementary school students.